Unprecedented Ultra‐High Expansion Ratio Foam for Innovative Architecture - Wenyu Zhong; Yichong Chen; Dongdong Hu; Jiayang Sun; Xingyu Jia; Ling Zhao (Advanced Science)
Abstract Global climate warming has dramatically increased the demand for space cooling. Materials that integrate superior thermal insulation with passive daytime radiative cooling properties hold significant promise for reducing energy consumption for space cooling during hot summers. In this study, conduction‐microwave heating assisted CO2 foaming process is used to optimize cell size and expansion ratios, producing PMMA/PVDF foam with an ultra‐high expansion ratio of 120 times and small, uniform cells. The foam is hydrophobic, chemically resistant, and recyclable, with a negative Poisson's ratio structure that gives it outstanding compression strength, elasticity, and flexibility, making it suitable for both everyday use and extreme weather conditions. The inherent properties of the material and its cell structure confer low thermal conductivity (26.69 mW m−1 K−1), high solar reflectance (96.37%), and high infrared emissivity (97.34%). This means that indoor cooling of buildings can be achieved in hot weather (15 °C difference in test results before and after use), meeting the cooling needs of buildings in most countries around the world. The ultra‐high expansion ratio PMMA/PVDF foam demonstrates significant potential in energy conservation, reducing carbon footprints, and promoting sustainability, providing a solution for the development of next‐generation buildings.